Ephrin expression and function in cancer. (January 2010) - McCarron, Jennifer K; Stringer, Brett W; Day, Bryan W; Boyd, Andrew W
Ephrins are cell membrane-associated signaling proteins bound by transmembrane Eph receptors on juxtaposed cells. Eph––ephrin interactions result in bidirectional signaling within both receptor- and ligand-bearing cells, with diverse consequences for cell morphology and behavior. Such interactions are especially important during early vertebrate development, and growing evidence has revealed equally important roles in adult-tissue homeostasis. As for the Eph receptors, abnormal expression of ephrins is associated with disease, especially cancer. The ephrins have received less attention than the Ephs in the literature, owing, in part, to their later discovery and that they are fewer in number. Here, we attempt to redress this imbalance and provide an ''ephrin-centric'' discussion of the expression and function of ephrins in cancer.